Land and power in Ptolemaic Egypt : the structure of land tenure - Manning, Joseph Gilbert (Cambridge University Press, 2003)
"This history of land tenure under the Ptolemies explores the relationship between the new Ptolemaic state and the ancient traditions of landholding and tenure. Departing from the traditional emphasis on the Fayyum, it offers a coherent framework for understanding the structure of the Ptolemaic state, and thus of the economy as a whole. Drawing for the first time on both Greek and demotic papyri, as well as hieroglyphic inscriptions and theories taken from the social sciences, Professor Manning argues that the traditional central-state "despotic" model of the Egyptian economy is insufficient. The result is a subtler picture of the complex relationship between the demands of the new state and the ancient, locally-organized social structure of Egypt. By revealing the dynamics between central and local power in Egypt, the book shows that Ptolemaic economic power ultimately shaped Roman Egyptian social and economic institutions."--Jacket